The Antecedents and Consequences of Net Promoter Score : The Case of an Energy Company - Brandejs, Matěj (2019)
The thesis analyses relationships between the Net Promoter Score (NPS) andantecedents and consequences that scholars claim related, using the case of an energycompany. Analysed relationships are with customer loyalty, price sensitivity,consumption, willingness to resume contracts, customer’s age, gender, educationallevel and geographic location. The goal is to confirm or reject these relationships usingstatistical methods of correlation analysis, analysis of variance, statistical testing andcontingency analysis on NPS surveys of the energy company. The results confirmrelationships with customer loyalty, willingness to resume contracts, price sensitivity,gender and educational level. Better insights emerge while focusing on the threecustomer categories defined by NPS rather than the direct link to NPS.